Climate Change and Economic Justice: The Impact of Environmental Degradation on Indonesia’s Vulnerable Populations (Indonesian Economic Justice Review, 2025)
This paper examines the intersection of climate change and economic justice in Indonesia, focusing on how environmental degradation exacerbates vulnerabilities among marginalized populations. Indonesia is highly vulnerable to climate change, with rising sea levels, extreme weather events, and deforestation threatening the livelihoods of millions, particularly those in rural, coastal, and indigenous communities. The study investigates the economic impact of climate change on vulnerable groups, including farmers, fishers, and urban slum dwellers, who often lack the resources to adapt to environmental shocks. The paper also evaluates the government’s response to climate change through adaptation policies, disaster relief programs, and the promotion of sustainable development practices. It critiques the effectiveness of these policies in addressing the disproportionate impacts on marginalized communities and proposes that economic justice should be central to Indonesia’s climate action plans. By analyzing the role of environmental policies in promoting or hindering equitable development, the paper argues that climate justice must be integrated into the broader economic agenda, with a focus on fair access to resources, technology, and social protections for the most vulnerable. The paper concludes by calling for more inclusive climate adaptation strategies and policies that prioritize the needs of Indonesia’s poorest and most vulnerable populations.